Estudio de factibilidad para la creación de la empresa “Confecciones Princes”, destinada a la fabricación y comercialización de ropa para niñas bajo el concepto de princesas, en los estratos 2, 3 y 4 del municipio de Supia Caldas (2015)
This document collects information concerning the development of a feasibility study to create a company called "Clothing Princes", intended for the manufacture and marketing of clothing for girls under the concept of princesses, levels 2, 3 and 4 of the municipality of Supía Caldas, in this way arises the general objective that has to do with the completion of each of the studies as: the study of market, technical, organizational, legal, environmental and financial. In the same way is the methodological development; as it is the type of study, population, sample, sources and techniques of collection of the information, as well as the budget and schedule of activities to run the investigation. The population niche which can be reached with this type of product, being the children of females between 5 and 14 years of age who are the people who demand this type of elements in greater proportion was established in the market study, analyzed also offer, marketing channels, price, promotion and advertising for the new company. The technical study examines the initial size of the company, the more appropriate location that could be given to the production unit as well as the engineering of the project. The administrative study considers the strategic direction, mission, vision, corporate values, organizational structure, description of positions and functions. The legal study examines the form of Constitution of the company, leaning by a SAS, which is offered best guarantees for the implementation of the project, in the same way is made an analysis of the environmental, i.e. of the environmental impact that would lead the new company in the environment, i.e. in the town of Supía Caldas. Finally analyzed through a structure of costs, expenses and income, financial flows of the project, the return on investment, which confirms the attractiveness of a kind of project of these conditions.